2005
DOI: 10.1242/jeb.01476
|View full text |Cite
|
Sign up to set email alerts
|

Glucose production and substrate cycle activity in a fasting adapted animal, the northern elephant seal

Abstract: During prolonged fasting physiological mechanisms defend lean tissue from catabolism. In the fasting state, glucose is derived solely from gluconeogenesis, requiring some catabolism of amino acids for gluconeogenic substrates. This creates a conflict in animals undergoing fasts concurrently with metabolically challenging activities. This study investigated glucose metabolism in fasting and developing neonatal elephant seals. Glucose production and glucose cycle activity were measured early (2 weeks) and late (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
86
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 49 publications
10
86
5
Order By: Relevance
“…Previous studies have demonstrated dramatic increases in serum cortisol concentrations during fasting duration in weaned pups and lactating females (Champagne et al, 2005;Ortiz et al, 2001). This pattern was thought to reflect increased needs for lipolysis during lactation and development (Fowler et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have demonstrated dramatic increases in serum cortisol concentrations during fasting duration in weaned pups and lactating females (Champagne et al, 2005;Ortiz et al, 2001). This pattern was thought to reflect increased needs for lipolysis during lactation and development (Fowler et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…All assays have been validated for use in elephant seals (Champagne et al, , 2005Ensminger et al, 2014;Ortiz et al, 2001). Mean intra-assay CV% were <3.5% and mean inter-assay CV% were <5.6% for all analytes.…”
Section: Hormone Analysesmentioning
confidence: 99%
“…The greater loss of lean tissue in breeding male elephant seals relative to that observed in post-molt, fasting weanlings (Houser and Costa, 2001) and simultaneously fasting and lactating females (Crocker et al, 1998) may support this proposition provided lean tissue catabolism supports gluconeogenesis. However, high rates of glucose recycling, as suggested in weaned pups and lactating females (Champagne et al, 2005;, may reduce impacts of GH suppression on commitment of amino acids to glucose production.…”
Section: Discussionmentioning
confidence: 99%
“…Observations in weaned elephant seal pups suggest that declining I/G ratios while fasting result from increased glucagon levels coupled with either declining or stable insulin levels (Ortiz et al, 2003;Champagne et al, 2005). In contrast, lactating female elephant seals achieve reductions in I/G ratios while fasting through suppression of insulin alone (Champagne et al, 2006;Houser et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation